Combined Local Blood–Brain Barrier Opening and Systemic Methotrexate for the Treatment of Brain Tumors. Issue 6 (June 2015) - Cooper, Itzik; Last, David; Guez, David; Sharabi, Shirley; Goldman, Shirin Elhaik; Lubitz, Irit; Daniels, Dianne; Salomon, Sharona; Tamar, Gregory; Tamir, Tzur; Mardor, Ronni; Fridkin, Mati; et al.
Despite aggressive therapy, existing treatments offer poor prognosis for glioblastoma multiforme patients, in part due to poor penetration of most drugs across the blood–brain barrier (BBB). We propose a minimal-invasive combined treatment approach consisting of local BBB disruption in the tumor in parallel to systemic drug administration. Local BBB disruption is obtained by convection-enhanced delivery of a novel BBB disruption agent, enabling efficient/targeted delivery of the systemically administered drug by the tumors own vasculature. Various human serum albumin (HSA) analogs were synthesized and screened for BBB disruption efficacy in custom in vitro systems. The candidate analogs were then delivered into naïve rat brains by convection-enhanced delivery and screened for maximal BBB disruption and minimal brain toxicity. These studies found a noncationized/neutralized analog, ethylamine (EA)–HSA, to be the optimal BBB-opening agent. Immunocytochemical studies suggested that BBB disruption by EA–HSA may be explained by alterations in occludin expression. Finally, an efficacy study in rats bearing intracranial gliomas was performed. The rats were treated by convection-enhanced delivery of EA–HSA in parallel to systemic administration of Methotrexate, showing significant antineoplastic effects of the combined approached reflected in suppressed tumor growth and significantly ( x3) prolonged survival.